TRUE GLUCOSE CONTENT OF LUMBAR AND VENTRICULAR CEREBROSPINAL FLUID - Marks, Vincent (1960)
Glucose levels in 154 random specimens of lumbar cerebrospinal fluid, normal as regards cell and protein content, were estimated by the glucose-oxidase method and a mean value of 60.5 mg./100 ml. (S.D. 7.3) was obtained. In 33 fasting patients subject to air encephalography the mean cerebrospinal fluid (C.S.F.) glucose level was 56.5 mg., and mean blood glucose level 65.5 mg. with an average C.S.F. glucose: blood glucose ratio of 0.85.